Influence of Rhizoctonia solani and Trichoderma spp. in growth of bean (Phaseolus vulgaris L.) and in the induction of plant defense-related genes - Mayo, Sara; Gutierrez, Santiago; Malmierca, Monica G.; Lorenzana, Alicia; Campelo, María P.; Hermosa, Rosa; Casquero, Pedro A. (Frontiers in Plant Science, 2015)
Many Trichoderma species are well-known for their ability to promote plant growth and defence. We study how the interaction of bean plants with R. solani and/or Trichoderma affect the plants growth and the level of expression of defence-related genes. Trichoderma isolates were evaluated in vitro for their potential to antagonize R. solani. Bioassays were performed in climatic chambers and development of the plants was evaluated. The effect of Trichoderma treatment and/or R. solani infection on the expression of bean defence-related genes was analysed by real-time PCR and the production of ergosterol and squalene was quantified. In vitro growth inhibition of R. solani was between 86% and 58%. In In in vivo assays, the bean plants treated with Trichoderma harzianum T019 always had an increased size respect to control and the plants treated with this isolate did not decrease their size in presence of R. solani. The interaction of plants with R. solani and/or Trichoderma affects the level of expression of seven defence-related genes. Squalene and ergosterol production differences were found among the Trichoderma isolates, T019 showing the highest values for both compounds. T. harzianum T019 shows a positive effect on the level of resistance of bean plants to R. solani. This strain induces the expression of plant defence-related genes and produces a higher level of ergosterol, indicating its ability to grow at a higher rate in the soil, which would explain its positive effects on plant growth and defence in the presence of the pathogen.